Papillary Laryngeal Carcinoma Presenting as Laryngeal Obstruction and Fatal Intractable Hypoxemia - Elizabeth Dacey; O John Ma; Peter Stenzel (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Unexpected acute laryngeal obstruction is most often caused by foreign bodies or edema and rarely by cysts, infection, or neoplasia. Neoplastic cases include soft tissue tumors and benign epithelial tumors. We report a case of fatal, unexpected, sudden asphyxia due to laryngeal obstruction by a papillary squamous cell carcinoma, a unique presentation of laryngeal squamous cell carcinoma and in this case an unusual histologic pattern. A 61-year-old man experienced respiratory distress while at work. Laryngeal obstruction was discovered in the emergency department. Cricothyrotomy was performed, but his blood oxygen saturation levels failed to improve and he died after a prolonged resuscitation. Autopsy revealed a papillary squamous cell carcinoma on the inferior aspect of the right vocal fold. We suggest that this unusual presentation of laryngeal carcinoma may be due to the unusual histologic features of the tumor.